Mengkaji Persepsi Umat Tentang Perayaan Ekaristi Harian dan Dampaknya Terhadap Partisipasi Umat di Kuasi Paroki ST. Petrus dan Paulus Oesapa - Agnes Anggiyanty Elma Un Tahu; Yohanes Rusae; Graciana Amanda Bele (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study was motivated by the low level of participation among the faithful in attending daily Eucharistic celebrations at Sts. Peter and Paul Quasi-Parish Oesapa. Many members of the congregation have not yet fully understood the meaning and significance of the daily Eucharist as the source and summit of Christian life. This study aims to examine the faithful’s understanding of the daily Eucharistic celebration, identify the factors that support and hinder their participation, and explore possible efforts to enhance their participation in daily Eucharistic celebrations. The study employed a qualitative research method with a descriptive approach. Data were collected through observation, interviews, and documentation. The participants included the Quasi-Parish Priest, a BHK seminarian, the Head of the Liturgy Commission, as well as parishioners who regularly attended daily Eucharistic celebrations, those who attended occasionally, and those who rarely participated. The findings reveal that many participants perceive the daily Eucharist as a source of spiritual strength, a means of drawing closer to God, and an opportunity to deepen their faith. However, some still consider daily Mass to be a non-essential aspect of their spiritual life. Factors supporting participation include personal faith awareness, spiritual habits, and the desire to attain inner peace. In contrast, the main obstacles include work commitments, household responsibilities, limited understanding of the importance of daily Mass, distance from the church, and physical conditions. The study concludes that the faithful’s perception of the daily Eucharistic celebration significantly influences their level of participation in the life of the Church. A deeper understanding of the meaning of the daily Eucharist leads to greater participation in daily Eucharistic celebrations.